The Impact of the Availability of Technological Infrastructure on the Success of the Electronic Document Management System of the Palestinian Pension Authority - Mohammed Khair I. Kassab; Samy S. Abu Naser; Mazen J. Al Shobaki (International Journal of Engineering and Information Systems (IJEAIS), 2017)
The aim of the study is to identify the impact of the technological infrastructure on the success of the electronic document management system of the Palestinian Pension Authority. In order to achieve the objectives of the study, the researchers used the analytical descriptive method in which it tries to describe the phenomenon studied, analyze its data, the relationship between its components and the opinions that are raised around it, and use the method of Complete Census due to the small size of the study community and accessibility to the target group. The researchers distributed (108) questionnaires to the community of this study, consisting of (65) employees in the Gaza Strip and (43) employees in the West Bank, and all the questionnaires were retrieved. The results of the study reached the following results: The study community agreed on the availability of the infrastructure of the Authority, where the ratios ranged from good to very good. Generally, the average mean of the axes was 4.09 and a relative weight of 82.0%. This result confirms the Authority's ability to provide suitable infrastructure and its ability to adapt to the electronic document management system, divided into: the employment of the latest computers to work in the Authority, and a relative weight of (83.5%). And provide the latest software and databases to work in the Authority, and a relative weight of (85.5%). The provision of computer network linking all the departments of the Authority with a relative weight of (77.0%). Members of the study community agreed that the electronic document system requires special technical skills and resistance from some of the jobs and specialties of the Authority who do not want to deal with the computer. Furthermore, the electronic documentation system would reduce the cost of the current system and would reduce the tasks assigned to staff members of different jobs. The study has reached a number of recommendations, the most important of which is: The Authority should endeavor to increase and develop its services for retirees, especially after the incorporation of private sector institutions and universities and opening the door to all sectors of society in Gaza and the West Bank and enhance its competitiveness among the international social security institutions. The need to hold training sessions and workshops for senior administrative levels to raise awareness of the culture and concepts of electronic document management system, including the general managers and managers as a first stage, which then extends to the lower administrative levels. Enhance the interest in the existence of a central computer network linking the main office in Gaza with the rest of the branches in the West Bank in order to ensure the implementation of the electronic document management system and the ability to hold meetings via videoconferencing and the ability to exchange electronic data copies. Promote the attention to the website of the Authority and activate it to be able to provide electronic services; by linking to an interactive database, dissemination of plans, policies, decisions, generalizations, objectives, the latest activities, news, and create an email to all employees in order to allow them to e-mail by automating all transactions with the electronic management documents system.
Keywords: 330; Technology Infrastructure; Electronic Document Management System; Palestinian Pension Authority; State of Palestine